Turismo accesible para personas con discapacidad auditiva y el desarrollo del turismo en los museos Públicos del Distrito de Iquitos en el 2023 - Dávila García, Victoria Gabriel (2025)
The research aimed to determine the relationship between accessible tourism for people with hearing disabilities and the development of tourism in the Public Museums of the Iquitos District in 2023. Developing under a basic research, descriptive-correlational level and non-experimental design, taking as population 56 people to whom a survey was applied to collect information. According to the results, 36% consider that accessible tourism is inadequate, this is mainly due to the fact that, in museums, the signage is usually not clear or easy to follow for those with hearing disabilities. In addition, museums rarely offer QR codes with accessible information and staff are almost never trained to serve these people. On the other hand, the development of tourism in the region was rated as regular by 29% of respondents. This indicates that continuous investments have been made in the infrastructure of public museums in Iquitos to improve access for people with disabilities. Likewise, on certain occasions, the promotion of accessible tourism has contributed to increasing the economic income of the city's museums. Finally, a significant and moderately strong correlation is established between the variables (coefficient of 0.694) and a significance of 0.000.